Heteroatom co-doped green pea peel-derived biochar for high-performance energy storage applications - Makinde, Wasiu Olakunle; Hassan, Mohsen A.; Semida, Wael M.; Pan, Ying; Guan, Guoqing; Lopez Salas, Nieves; Khalil, Ahmed S. G. (RSC Advances)
Green pea peel (GPP) is a waste, and it is abundant and available to be used for biochar synthesis.

Toward high-density streptavidin arrays on DNA origami nanostructures - Rabbe, Lukas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (RSC Advances)
Streptavidin binding to DNA origami-supported high-density biotin arrays is investigated for selected experimental parameters. While bidentate binding and steric hindrance can be minimized, molecular crowding limits the binding yields in 2D arrays.

Self-immolative polydisulfides and their use as nanoparticles for drug delivery systems - Völlmecke, Katharina; Kramer, Maurice; Horky, Corinna; Dückmann, Oliver; Mulac, Dennis; Langer, Klaus; Kuckling, Dirk (RSC Advances)
Over the last few decades, nanotechnology has established to be a promising field in medicine. A remaining dominant challenge in today's pharmacotherapy is the limited selectivity of active pharmaceutical ingredients and associated undesirable side effects. Controlled drug release can be promoted by smart drug delivery systems, which release embedded API primarily depending on specific stimuli. Consequently, also the microenvironment of tumor tissue can be used advantageously. Dithiothreitol (DTT) based self-immolative polydisulfides were synthesized that preferentially respond to pathologically increased glutathione (GSH) concentrations, as found in solid tumors. The synthesis with different degrees of polymerisation was investigated as well as the synthesis of a copolymer consisting of dithiothreitol and butanedithiol (BDT). Toxicity tests were carried out on pure polymers and their degradation products. The ability to degrade was examined at pathological and physiological glutathione concentrations in order to test the suitability of the polymer as a matrix for nanoparticulate carrier systems. In addition, the processability of one polymer into nanoparticles was investigated as well as the degradation behaviour with glutathione.

Hard carbon microspheres with bimodal size distribution and hierarchical porosity via hydrothermal carbonization of trehalose - Wortmann, Martin; Keil, Waldemar; Diestelhorst, Elise; Westphal, Michael; Haverkamp, René; Brockhagen, Bennet; Biedinger, Jan; Bondzio, Laila; Weinberger, Christian; Baier, Dominik; Tiemann, Michael; Hütten, Andreas; et al. (RSC Advances)
Hydrothermal carbonization (HTC) is an efficient thermochemical method for the conversion of organic feedstock to carbonaceous solids. HTC of different saccharides is known to produce microspheres (MS) with mostly Gaussian size distribution, which are utilized as functional materials in various applications, both as pristine MS and as a precursor for hard carbon MS. Although the average size of the MS can be influenced by adjusting the process parameters, there is no reliable mechanism to affect their size distribution. Our results demonstrate that HTC of trehalose, in contrast to other saccharides, results in a distinctly bimodal sphere diameter distribution consisting of small spheres with diameters of (2.1 ± 0.2) μm and of large spheres with diameters of (10.4 ± 2.6) μm. Remarkably, after pyrolytic post-carbonization at 1000 °C the MS develop a multimodal pore size distribution with abundant macropores > 100 nm, mesopores > 10 nm and micropores < 2 nm, which were examined by small-angle X-ray scattering and visualized by charge-compensated helium ion microscopy. The bimodal size distribution and hierarchical porosity provide an extraordinary set of properties and potential variables for the tailored synthesis of hierarchical porous carbons, making trehalose-derived hard carbon MS a highly promising material for applications in catalysis, filtration, and energy storage devices.
Keywords: General Chemical Engineering; General Chemistry

Hard carbon microspheres with bimodal size distribution and hierarchical porosity via hydrothermal carbonization of trehalose - Wortmann, Martin; Keil, Waldemar; Diestelhorst, Elise; Westphal, Michael; Haverkamp, René; Brockhagen, Bennet; Biedinger, Jan; Bondzio, Laila; Weinberger, Christian; Baier, Dominik; Tiemann, Michael; Hütten, Andreas; et al. (RSC Advances)
Hydrothermal carbonization of trehalose, in contrast to other saccharides, leads to the formation of microspheres with a bimodal size distribution. The microspheres develop hierarchical porosity with micro-, meso-, and macro-pores after pyrolysis.

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Filvan Torkaman, Najmeh; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Protonation-induced charge transfer and polaron formation in organic semiconductors doped by Lewis acids - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (RSC Advances)
Lewis-acid doping of organic semiconductors (OSCs) opens up new ways of p-type doping and has recently become of significant interest.
Keywords: General Chemical Engineering; General Chemistry

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Torkaman, Najmeh Filvan; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Protonation-induced charge transfer and polaron formation in organic semiconductors doped by Lewis acids - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (RSC Advances)
Lewis-acid doping of organic semiconductors (OSCs) opens up new ways of p-type doping and has recently become of significant interest.
Keywords: General Chemical Engineering; General Chemistry

Analysis of sequence-defined oligomers through Advanced Polymer Chromatography™ – mass spectrometry hyphenation - Berg, Marie-Theres; Mertens, Chiel; Du Prez, Filip; Kühne, Thomas D.; Herberg, Artjom; Kuckling, Dirk (RSC Advances)

A photoredox catalysed Heck reaction via hole transfer from a Ru(ii)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg; Gerstmann, Uwe; Meier, Armin; Schmidt, Wolf Gero; Wilhelm, René (RSC Advances)
A hole transfer from an excited Ru unit towards graphene oxide significantly improved the photocatalytic activity of the complexes.
Keywords: General Chemical Engineering; General Chemistry

Surface modification of ZnMgAl-coated steel by dielectric-barrier discharge plasma - Knust, Steffen; Kuhlmann, Andreas; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (RSC Advances)
Correlation between atmospheric DBD plasma-induced surface chemical changes on a ZnMgAl alloy coating and the resulting adhesive properties.

Water assisted atomic layer deposition of yttrium oxide using tris(N,N′-diisopropyl-2-dimethylamido-guanidinato) yttrium(iii): process development, film characterization and functional properties - Mai, Lukas; Boysen, Nils; Subaşı, Ersoy; de los Arcos de Pedro, Maria Teresa; Rogalla, Detlef; Grundmeier, Guido; Bock, Claudia; Lu, Hong-Liang; Devi, Anjana (RSC Advances)
A new water assisted atomic layer deposition (ALD) process was developed using the yttrium tris-guanidinate precursor which resulted in device quality thin films.

Copolymerization of CO2 and epoxides mediated by zinc organyls - Wulf, Christoph; Doering, Ulrike; Werner, Thomas (RSC Advances)
Simple zinc organyls (R2Zn) efficiently catalyze the copolymerization of CO2 and cyclohexene oxide. The effect of various reaction parameters has been studied. The reaction proceeds under halogen-free conditions and no co-catalyst is required.
Keywords: T1; T3; CSSD

Gels, xerogels and films of polynuclear iron(ii)–aminotriazole spin-crossover polymeric complexes - Sánchez-Ferrer, Antoni; Bräunlich, Irene; Ruokolainen, Janne; Bauer, Matthias; Schepper, Rahel; Smith, Paul; Caseri, Walter; Mezzenga, Raffaele (RSC Adv.)
Keywords: General Chemical Engineering; General Chemistry

New spinel oxide catalysts for visible-light-driven water oxidation - Conrad, Franziska; Bauer, Matthias; Sheptyakov, Denis; Weyeneth, Stephen; Jaeger, Dominik; Hametner, Kathrin; Car, Pierre-Emmanuel; Patscheider, Jörg; Günther, Detlef; Patzke, Greta R. (RSC Advances)
Keywords: General Chemical Engineering; General Chemistry